Respuestas
Respuesta dada por:
1
solución:
-x-10=-8+10 despejando para x
8-10-10=x
-12=x
4-2=1-z despejando para z
z=1+2-4
z=-1
-x+3=7 despejando para x
3-7=x
-4=x
2+3=y+1 despejando para y
2+3-1=y
4=y
Espero haberte ayudado
-x-10=-8+10 despejando para x
8-10-10=x
-12=x
4-2=1-z despejando para z
z=1+2-4
z=-1
-x+3=7 despejando para x
3-7=x
-4=x
2+3=y+1 despejando para y
2+3-1=y
4=y
Espero haberte ayudado
Preguntas similares
hace 6 años
hace 6 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años